A Whooper Swan Cygnus cygnus population wintering at Kilcolman Wildfowl Refuge, Co. Cork, Ireland: trends over 20 years - O'Halloran, J; Ridgway, M; Hutchinson, C D (Wildfowl, 1993)
Whooper Swans have been counted daily at Kilcolman Wildfowl Refuge, Co. Cork, Ireland, from 1971 to 1990. An analysis of this 20 years of data, including first arrival and departure dates, duration of stay, and general population trends, is presented. The median number of birds has been increasing over the last 20 years at a rate of approximately 6% per annum. The first arrival date varies by 46 days from 1 October to 15 November with a mean duration of stay of 174 days. The largest numbers occur in Spring in most years. The importance of Kilcolman Wildfowl Refuge for Whooper Swans in Ireland is discussed.